Tailoring palladium nanocontacts by electromigration - Arzubiaga, Libe (2013)
Electromigration is employed in nanoelectronics for transforming narrow metallic wires into electrodes separated by a few nanometers gap. In this work, we fabricate either nanoconstrictions or nanogap electrodes by performing electromigration in palladium nanowires. The device resistance and the cross section of the initial nanowires allow us to regulate the conditions for transforming deterministically each nanowire in a specific final device. The resulting samples show unique electrical transport characteristics and could be used in multiple nanoelectronics research applications, from ballistic transport to electrodes for single molecular devices.